Skills, Perceived Knowledge and Training on the Effectiveness of Using Accounting Information Systems - Ni Luh Intan Chintya Cahyani; I Made Pande Dwiana Putra (E-Jurnal Akuntansi, 2024)
The aim of this study was to collect empirical evidence and determine the influence of skill, perceived knowledge, and training on the effectiveness of using accounting information systems. This study was conducted at Ungasan Village Savings and Loan Cooperative. This study used several linear analysis techniques. To determine the sample, this study uses non-probability sampling method with intentional sampling technique. The sample has up to 68 respondents. The results of the analysis show that skills, knowledge awareness and training have a positive effect on the effectiveness of using accounting information systems. The implication of this research is to provide empirical support for the Technology Acceptance Model theory and provide benefits for savings and loan cooperatives in Ungasan Village so that they can prioritize the personal abilities of each employee with a background assessment.